2001
DOI: 10.1007/s004670100003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of renal function in recipients and donors following pediatric kidney transplantation

Abstract: Of 125 children undergoing kidney transplantation (tx), 87 received their grafts from living donors. Renal function of recipients (R) and donors (D) was assessed by glomerular filtration rate (GFR) and effective renal plasma flow (ERPF) determined by clearances of inulin and para-aminohippuric acid. Rs were investigated yearly and Ds on alternate years. Within 5 months of tx, absolute GFR and ERPF (ml/min) were significantly lower in R than in D, and the differences in absolute GFR and ERPF between D and R wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that the increases in GFR and eRPF in the remaining kidney following donation are maintained over many years [24]. Bugge et al studied eight donors over the immediate 24 h post-nephrectomy [25]; GFR and eRPF increased by 70 % within 1 h and was maintained over 24 h. Pabico et al reported mean post-nephrectomy GFR increase of 37 % and mean eRPF of 55 %; the FF was not significantly different pre-and post-nephrectomy [26], similar to the results reported by Tent et al [27].…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that the increases in GFR and eRPF in the remaining kidney following donation are maintained over many years [24]. Bugge et al studied eight donors over the immediate 24 h post-nephrectomy [25]; GFR and eRPF increased by 70 % within 1 h and was maintained over 24 h. Pabico et al reported mean post-nephrectomy GFR increase of 37 % and mean eRPF of 55 %; the FF was not significantly different pre-and post-nephrectomy [26], similar to the results reported by Tent et al [27].…”
Section: Discussionmentioning
confidence: 97%
“…For this reason, larger prospective studies should be done in paediatric renal transplant recipients to evaluate ambulatory BP, lipid profile and left ventricular mass [37]. Third, in investigations performed in renal transplant recipients it would be of utmost importance that the interpretation of renal function relies on an accurate method to measure glomerular filtration rate, such as the inulin clearance test [38]. However the Schwartz formula, when followed serially, should still allow group comparisons [26].…”
Section: Discussionmentioning
confidence: 98%
“…The glomerular filtration rate (GFR) was measured by renal clearance of inulin, using the standard clearance technique during water diuresis and continuous infusion [21,22], or plasma clearance of iohexol, using the slope curve.…”
Section: Methodsmentioning
confidence: 99%